Hard X‐Ray Photoemission Study of Heusler‐Type Fe2−xRexVAl Thermoelectric Compounds. Issue 9 (26th April 2022) - Asai, Monami; Miyazaki, Hidetoshi; Watanabe, Kosuke; Yasui, Akira; Takagi, Yasumasa; Nishino, Yoichi
Abstract : The electronic structure of Fe2− x Re x VAl compounds is investigated using bulk‐sensitive hard X‐ray photoelectron spectroscopy (HAXPES) measurements and electronic band calculations to elucidate the origin of the improvement in their thermoelectric properties. The HAXPES results show that, with the substitution of Re atoms for the Fe site, a new Re 5 d state appears near the Fermi level, which leads to a change in the electronic structure with a gradual narrowing of the pseudo‐gap. The decrease in the pseudo‐gap width with Re substitution is found to be related to the increase in the p ‐type Seebeck coefficient and the shift in its peak temperature to the lower temperature side. Abstract : The electronic structure of Fe2− x Re x VAl thermoelectric compounds is investigated using bulk‐sensitive hard X‐ray photoelectron spectroscopy (HAXPES) measurements and electronic band calculations. The decrease in the pseudo‐gap width with Re substitution is related to the increase in the p ‐type Seebeck coefficient and the shift in its peak temperature to the lower temperature side.